Measurement of top quark polarization in top-antitop events from proton-proton collisions at √s=7 TeV using the ATLAS detector - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; et al. (Physical review letters, 2013)
This Letter presents measurements of the polarization of the top quark in top-antitop quark pair events, using 4.7 fb(-1) of proton-proton collision data recorded with the ATLAS detector at the Large Hadron Collider at √s=7 TeV. Final states containing one or two isolated leptons (electrons or muons) and jets are considered. Two measurements of α(ℓ)P, the product of the leptonic spin-analyzing power and the top quark polarization, are performed assuming that the polarization is introduced by either a CP conserving or a maximally CP violating production process. The measurements obtained, α(ℓ)P(CPC)=-0.035±0.014(stat)±0.037(syst) and α(ℓ)P(CPV)=0.020±0.016(stat)(-0.017)(+0.013)(syst), are in good agreement with the standard model prediction of negligible top quark polarization.